2016
DOI: 10.1007/s13201-016-0497-x
|View full text |Cite
|
Sign up to set email alerts
|

Recharge source identification using isotope analysis and groundwater flow modeling for Puri city in India

Abstract: The holy city of Lord Jagannath is situated on the sea shore of the Bay of Bengal in Odisha state in India. Puri is a city of high religious importance and heritage value, details of the rituals, fairs, and festivals, and related aspects are covered extensively. It is found that water levels in two wells (Ganga and Yamuna) are declining and the causes are studied by undertaking modeling study of rainfall-recharge processes, surface water-groundwater interactions, and increasing demands due to urbanization at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
3
8
0
Order By: Relevance
“…Based on the results and the analysis of the SPI index, the surveyed area was categorized as experiencing normal drought conditions. These ndings align with previous studies by [30], [39], and [24]. Climate classi cation results from three synoptic stations in the region indicated that the area falls within the semi-arid climatic category.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the results and the analysis of the SPI index, the surveyed area was categorized as experiencing normal drought conditions. These ndings align with previous studies by [30], [39], and [24]. Climate classi cation results from three synoptic stations in the region indicated that the area falls within the semi-arid climatic category.…”
Section: Discussionsupporting
confidence: 92%
“…The different input layers, i.e., recharge, boundary conditions, well locations, and hydraulic conductivity, have been input to create a model using Visual MODFLOW [16]. This deterministic numerical model is based on Darcy's law and mass conservation concept.…”
Section: Methodsmentioning
confidence: 99%
“…The GRI index can explain groundwater drought properly. In some previous researches, such as Nayak et al, [56] the drought indices were only based on a normalization method. In their study they provided the precipitation data and groundwater level data for a catchment which had 541 wells.…”
Section: Discovering the Association Of Climatic With Hydro-meteorolomentioning
confidence: 99%